ERRATA do artigo "A cross-country non parametric estimation of the returns to factors of production and the elasticity of scale" - Marquetti, Adalmir (Nova Economia, 2011)
ERRATA do artigo "A cross-country non parametric estimation of the returns to factors of production and the elasticity of scale", de Adalmir Marquetti. (figuras 3, 5, 7, 9)